Patterns of Different Cervical Cytokine Expression in High-Risk Human Papillomavirus–Infected Patients With Cervical Cancer and Its Precancerous Lesions - Shamoli Saha; Sharmin Sultana; Raad Rahmat; Tahmina Akther; Ashrafun Nessa; Munira Jahan (Clinical Medicine Insights: Oncology)
Background: Cervical cancer is the second most common cancer in Bangladesh and is primarily caused by persistent high-risk human papillomavirus (HR-HPV) infection. Several risk factors, including immunological, genetic, environmental, and viral factors, may contribute to the development of cervical cancer. Moreover, a disruption in an otherwise delicate balance between immune response and cytokine production may lead to diseased states. Henceforth, this study aimed to determine and compare selected cytokines, including interleukin-6 (IL-6), interleukin-1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), interferon-gamma (INF-γ), interleukin-10 (IL-10), GM-CSF, interleukin-8 (IL-8), and MCP-1 among HR-HPV-infected patients with cervical cancer, precancer individuals, and healthy participants to test the propensity of these cytokines to serve as predictive biomarkers for the detection of cervical cancer during its early stages. Methods: A cross-sectional study was conducted on female patients visiting two referral hospitals in Bangladesh from September to November 2022. Among them, 80 women were enrolled in the study as patients with cervical cancer and precancerous lesions along with HPV DNA–negative healthy individuals. The selected cytokines in the cervical swab were estimated by flow cytometry. Result: Cervical cancer and precancer were primarily detected in patients aged above 40 years (73.3% and 46.7% of the patients in the respective groups). Other significant risk factors, including poor educational, socioeconomic status and nutritional conditions, age of first coitus, multiparity, and tobacco and betel nut consumption, were found significant for the development of cervical cancer and precancer ( P  < .05). The levels of IL-6, IL-1β, IL-10, IL-8, and MCP-1 were substantially elevated in patients with cancer than in patients with precancer and healthy individuals ( P  < .001). Moreover, the levels of IL-6, IL-1β, IL-10, and IL-8 were also significantly increased in patients with precancer than in healthy individuals ( P  < .05). Conclusions: Thus, IL-6, IL-1β, IL-10, IL-8, and MCP-1 can be used as potential biomarkers for diagnostic and prognostic purposes in HPV-induced cervical cancer and precancer.